Changing Teachers' Negative Attitudes Toward Persons With Intellectual Disabilities. (May 2015) - Hassanein, Elsayed Elshabrawy Ahmed
The current study aims at changing teachers' negative attitudes toward persons with intellectual disabilities. The intervention is based on the argument that providing information is not sufficient to achieve lasting change of attitudes toward people with disabilities, and that contact is required as an additional element to show positive results. A pretest-posttest intervention was conducted using three conditions: (a) cognitive intervention, (b) cognitive and behavioral intervention involving contact with the target group, and (c) no-intervention control. The participants comprised 18 teachers, with 6 teachers in each group. Following baseline assessments of attitudes, attitude change was measured immediately following the intervention and at a follow-up 12 weeks postintervention. The cognitive intervention provided information about intellectual disability and challenged stereotypic conceptions about persons with intellectual disabilities. The behavioral intervention involved being engaged in work with and training persons with intellectual disabilities in sheltered workshops. The results showed that the cognitive intervention alone did not result in significant changes in attitudes toward persons with intellectual disabilities. However, the combined cognitive-behavioral intervention resulted in greater attitude change than the no-intervention condition, both immediately postintervention and at a 12-week follow-up. The findings are discussed with regard to models of attitude change. The study concludes with some recommendations for teacher training programs to be attended to.